Implementasi Enkripsi AES Cipher dan Discrete Wavelet Transform Dalam Metode Steganografi - David Christ Antono; Henry Novianus Palit; Rudy Adipranata (Jurnal Infra, 2020)
The science of steganography leads to a branch of computer science that is about hiding data information in media that cannot be easily detected. There are many types of media for steganography. The most popular ones are digital images. Along with the development of the science of steganalysis, there is needs of a way to add security to the hidden data. With steganalysis, one can easily reveal existence of hidden data in media files. Therefore, this study seeks to answer the need for securing the data. The program is an application that is useful for securing hidden data. The function of this program is to encrypt data that will be hidden using the AES cipher method. By converting hidden data into ciphertext, even though hidden data can be taken its form is still in the form of text that cannot be read without using the key used to encrypt. This process involves data that will be hidden to be converted into ciphertext first and finally steganography will be performed using least significant bits. Not only that, the program will also compress stego image. From the results of the encryption, steganography and compression trials, the hidden image data can be retrieved using the key used during encryption. The hidden data does not experience loss of information because the process is carried out lossless. The hidden data has been compared with extracted data and produces unlimited PSNR values.